The role of FOCAC as institutional framework for China’s belt and road initiative projects in Ethiopia - Khatimah, Annisa Ridhatul (Privietlab, 2026)
When international relations have traditionally been shaped by hegemonic power politics that prioritize dominance over equality and mutual benefit, China–Africa relations have emphasized the principles of win–win cooperation institutionalized through the Forum on China–Africa Cooperation (FOCAC) since 2000. As a multilateral platform, FOCAC facilitates collective consultation and cooperation and has gained greater significance since the launch of China’s Belt and Road Initiative (BRI) project in 2013 as a mechanism for aligning Chinese initiatives with African development agendas. Interestingly, the agenda of FOCAC 2024 has shifted from a dominant focus on large-scale infrastructure toward more sustainable, socially oriented, and norm-driven cooperation, as a response to international criticism of the debt and the effectiveness of mega-infrastructure projects in some African states. Thus, this article analyzes the current role of FOCAC in the implementation of the BRI in Ethiopia, which has emerged as a key partner. Although several studies acknowledge FOCAC as a coordination platform, limited research systematically examines its institutional role in structuring cooperation between states. Using neoliberal institutionalism, this study argues that FOCAC reduces uncertainty, facilitates long-term cooperation, and shapes state behavior through repeated interactions, action plans, and reputational considerations. The findings demonstrate that despite its formal status as a diplomatic forum, FOCAC increasingly functions as a quasi-institution in stabilizing China–Ethiopia cooperation. However, the sustainability of this cooperation depends on China’s ability to generate tangible developmental benefits without exacerbating debt burdens or reinforcing structural asymmetries.